2010
DOI: 10.3144/expresspolymlett.2010.94
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and thermal stability of silk fibroin/starch blended microparticles

Abstract: Abstract. In the present study biodegradable microparticles of silk fibroin (SF)/starch blends were prepared by a simple water-in-oil emulsion solvent diffusion technique. SF/starch blended solution and ethyl acetate were used as water and oil phases, respectively. The influence of SF/starch ratios on characteristics of the blended microparticles was investigated. The SF conformation of microparticle matrices from FTIR analysis was changed from random coil to β-sheet form by blending with starch. The blended m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
(32 reference statements)
3
15
0
Order By: Relevance
“…loss of Dox-loaded spheres, observed till 100 ºC, could be attributed to the evaporation of water from the sample, which was mentioned in previous studies for silk based structures [66][67][68]. The main weight loss of H21MS1:MS1Fe1/IONPs/Dox particles took place in the temperature range of 250-750 ºC which may be associated with the decomposition of the side chain groups of the amino acid residues and the breakdown of peptide bonds [69].…”
Section: Discussionmentioning
confidence: 54%
“…loss of Dox-loaded spheres, observed till 100 ºC, could be attributed to the evaporation of water from the sample, which was mentioned in previous studies for silk based structures [66][67][68]. The main weight loss of H21MS1:MS1Fe1/IONPs/Dox particles took place in the temperature range of 250-750 ºC which may be associated with the decomposition of the side chain groups of the amino acid residues and the breakdown of peptide bonds [69].…”
Section: Discussionmentioning
confidence: 54%
“…The mixture then was padded on the fabric, the samples were dried at 105 °C to support coagulation and then were rinsed with water and dried. A temperature of 105 °C was chosen for drying as stability of fibroin is known to allow thermal treatments up to 150 °C . Fibroin deposition/fixation was assessed by direct observation of the color in case of RB19 marked fibroin.…”
Section: Resultsmentioning
confidence: 99%
“…A temperature of 105 8C was chosen for drying as stability of fibroin is known to allow thermal treatments up to 150 8C. 42 Fibroin ARTICLE WILEYONLINELIBRARY.COM/APP deposition/fixation was assessed by direct observation of the color in case of RB19 marked fibroin. In case of undyed fibroin staining with Comassie Blue was used to visualize the presence of the fibroin coating.…”
Section: Fibroin Regenerationmentioning
confidence: 99%
“…In addition, the position of amide I shifted, indicating that the hydroxyl group of alginate interacted with keratin. e Alg microparticle showed predominant broad peaks around 3399-2930 cm −1 due to O-H and C-H stretching and about 1038 cm −1 which is the saccharide backbone structure [21]. is revealed that the forces affected to form the Ker/Alg blend microparticles were hydrogen and negatively charged electrostatic forces [20].…”
Section: Secondary Structurementioning
confidence: 91%